2020
DOI: 10.1002/ijfe.2340
|View full text |Cite
|
Sign up to set email alerts
|

Environmental disaster and women self‐sustainability—A survey study on microfinance female clientele in Pakistan

Abstract: The prime objective of this study is to investigate the role of microfinance institutions towards women's self‐sustainability in Pakistan because women are the most vulnerable community in Pakistan and in the world, too. Due to various issues like gender discrimination, women's self‐sustainability is quite low, and this accounts for the negligible contribution of women in Pakistan's economy (up to 20 to 25%). In addressing this issue, the current study adopted a quantitative research approach and cross‐section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…The previous studies [ 15 , 19 ] found microfinance services assisting clients in starting new businesses had a favourable impact on ME growth and increased business activities. Clients of microfinance programmes experienced a growth in their microbusiness [ 40 ]. Similarly, Ul-Hameed et al [ 82 ] discovered that microfinance services have a favourable impact on the growth of businesses and the ability of low-income households to start new businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The previous studies [ 15 , 19 ] found microfinance services assisting clients in starting new businesses had a favourable impact on ME growth and increased business activities. Clients of microfinance programmes experienced a growth in their microbusiness [ 40 ]. Similarly, Ul-Hameed et al [ 82 ] discovered that microfinance services have a favourable impact on the growth of businesses and the ability of low-income households to start new businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The three main financial services offered by the microfinance programme are micro-credit, micro-savings, and micro-insurance. These services are often recognized as necessary for business growth, and development [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations